Numerical Modelling of the Draught Rate in a Mechanically Ventilated Climate Chamber. Issue 1 (January 2021) - Angelova, R A; Mijorski, S; Markov, D; Stankov, P; Velichkova, R; Simova, I
Abstract: The thermal environment in an indoor space is determined by the thermal state of the human body, and the local thermal discomfort. The draught rate (DR) is one of the indices for thermal discomfort. The achievement of air distribution without draught is one of the goals of the ventilation methods. It is especially important in the design of climate chambers, where the volume is small, and the research studies may require prolonged occupants' exposure. Our study shows results from the CFD simulations of a mechanically ventilated climate chamber, performed in the design stage of the chamber's construction. Velocity profiles distribution, temperature distribution and DR are used to assess the thermal comfort of the person in the chamber. The results obtained allowed designing of the proper indoor environment with desired characteristics for air distribution and human exposure.